PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA PT. SINAR PANTJA DJAJA SEMARANG) (Students' Journal of Economic and Management, 2013)
The purpose of the study entitled "The Effect of Leadership, Motivation and Job Satisfaction Performance Against PT. Sinar Pantja Djaja Semarang "is to analyze the leadership, motivation and job satisfaction on the PT. Sinar Pantja Djaja Semarang. The sample used in this study were 90 respondents to the data collection methods used in this research is using questionnaires (questionnaire) by spreading a list of questions to respondents in order to obtain information. The collected data were analyzed using factor analysis to test the validity of the item, the Cronbach alpha formula to test the reliability of the instrument, regression analysis, to examine the influence of each partial independent variables were tested with the coefficient of determination and prove the partial effect of each independent variable . It is known that the leadership, motivation and job satisfaction has a positive and significant influence on employee performence. The hypothesis has been done in this study we can conclude that There is a positive and significant effect of leadership on employee performance, There is a positive and significant effect of motivation on employee performance, and There is a positive and significant effect job satisfaction on employee performance. Keywords: Leadership, Motivation, Job Satisfaction, and Employee Performance